Measurements of bottom soil respiration in farming ponds for shrimp in La Barcés (Sucre), Colombian Caribbean - Echeverri, Alejandro Ramírez; Avnimelech, Yoram; Ibarra, Sergio Martínez; León, Ricardo Álvarez (Arquivos de Ciências do Mar, 2010)
Measurements of bottom soil respiration, water column respiration, and oxygen production were made in three different ponds stocked with Litopennaeus vannamei, with three different treatments of organic fertilization, described below: (A) 200 kg/ha of soy , during the bottom preparation, and 11 kg/ha of soy weekly; (B) 200 kg/ha, during the bottom preparation, and 11 kg/ha of soy weekly during the crop cycle, an extra application of inorganic fertilizer were made based on 10 kg/ha of DAP and ammonium nitrate during the preparation, follow by 2 kg/ha of DAP weekly during the first three weeks; (C) 50 kg/ha of soy, during the bottom preparation, and 23 kg/ha of soy applied weekly during the crop cycle. Bottom soil respiration was determined by benthos chambers, and clear and dark bottles methodology for water column respiration and production. The soil oxygen demand corresponds to 0.0395, 0.15 y 0.064 gr O2 m2 hr-1 , for each treatment A,B, and C. The average respiration in the water column for treatments A, B, and C, are 0.345, 0.364 y 0.368 g O2 m3 h-1 . Water column respiration was higher in treatments A,C, and lower in B. The values for oxygen production in the water column are 047, 0.814, y 1.028 g O2 m2 h-1 , for treatments A, B and C.